levels of CD4⁺CD25⁺ regulatory T cells in paediatric patients with allergic rhinitis and bronchial asthma - Lee, J.-H; Yu, H.-H; Wang, L.-C; Yang, Y.-H; Lin, Y.-T; Chiang, B.-L (Clinical and experimental immunology, 2007)
Our purpose was to determine whether numbers of CD4⁺CD25⁺ T [T regulatory (Treg)] cells and mRNA expression of functional molecules of Treg are related to airway allergy and disease severity in 51 paediatric patients with allergic rhinitis or bronchial asthma and 47 healthy controls. Surface markers were evaluated with flow cytometry, and mRNA was determined with real-time polymerase chain reaction. Children with allergic disease had fewer CD4⁺CD25⁺ T cells (8·49% ± 2·41% versus 9·58% ± 2·43%, P < 0·05) and CD4⁺CD25hi T cells (1·32% ± 0·68% versus 1·70% ± 0·68%, P < 0·01) than control subjects. Numbers of CD4⁺CD25⁺ and CD4⁺CD25hi T lymphocytes were higher in children with persistent allergic rhinitis and/or moderate-severe bronchial asthma than in those with respective milder disease. The number of Treg cells was correlated positively with total immunoglobulin E level. The mRNA expression of forkhead box P3 (FoxP3) was increased in moderate-severe versus mild asthma (2·93 ± 0·38 versus 1·60 ± 0·31, P < 0·01). Patients with moderate-severe bronchial asthma also had increased mRNA expression of interleukin (IL)-10 compared with patients with mild asthma (15·24 ± 4·07 versus 3·77 ± 2·18, P < 0·01). The suppressive function of Treg cells from patients with more severe asthma was competent in vitro. On average, decreased numbers of Treg cells in children with allergic airway disease might represent a defect of the Treg population. With increased expression of FoxP3 and IL-10 in Treg from patients with relatively severe allergic disease, adaptive and functional Treg might be generated in response to aggravated atopy and disease severity.